2023
DOI: 10.7717/peerj.14628
|View full text |Cite
|
Sign up to set email alerts
|

Chinese striped-neck turtles vocalize underwater and show differences in peak frequency among different age and sex groups

Abstract: Background Turtle vocalizations play an important role throughout their lives by expressing individual information (position, emotion, or physiological status), reflecting mating preferences, and synchronizing incubation. The Chinese striped-neck turtle (Mauremys sinensis) is one of the most widely distributed freshwater turtles in China, whose wild population is critically endangered. However, its vocalization has not been studied, which can be the basis for behavioral and ecological studies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…It is also worth noting that these free-moving turtles were only one-month-old suggesting that vocal complexity may increase during development and highlighting the necessity of studying the use of sounds in turtles across different life stages. Moreover, studies in freshwater turtles that were living in captivity as a group found that the use of sound types varies by sexes and ages [48][49][50]. These findings support our expectation that turtles have wider use of sounds in their underwater lives and suggest the potential of social communication by acoustic signals in turtles.…”
Section: Future Directions and Conclusionsupporting
confidence: 80%
See 3 more Smart Citations
“…It is also worth noting that these free-moving turtles were only one-month-old suggesting that vocal complexity may increase during development and highlighting the necessity of studying the use of sounds in turtles across different life stages. Moreover, studies in freshwater turtles that were living in captivity as a group found that the use of sound types varies by sexes and ages [48][49][50]. These findings support our expectation that turtles have wider use of sounds in their underwater lives and suggest the potential of social communication by acoustic signals in turtles.…”
Section: Future Directions and Conclusionsupporting
confidence: 80%
“…Thereafter, research in both sea turtles and freshwater turtles has revealed that eggs emit sounds during hatching, which may enable the synchronization of hatching among siblings (figure 2; table 2). The underwater sounds produced by turtles have recently been investigated in a handful of freshwater or marine turtle species (table 2), either free-ranging [38] or living in a group with conspecifics in captivity [39,42,43,[47][48][49]. When living in a group, the use of sound types can vary by sex and age [47][48][49], which The number of records of using sounds in behavioural contexts in non-avian reptiles over the past two decades.…”
Section: (B) Turtlesmentioning
confidence: 99%
See 2 more Smart Citations